Factors Influencing the Implementation of Detention Care Policy in the Environment of Banten Regional Police Department - Prayoga, Bayu Febrianto; Zulkarnain, Annas; Arya Anjaya, I Gusti Ngurah Agung; Kurniawan, Nur Arief (Faculty of Law, Universitas Pekalongan, 2024)
This study emphasizes the importance of the factors that influence the implementation of prisoner care policies that involve important and strategic components in supporting efforts to effectively implement prisoner care policies. The study uses a quantitative research approach to collect accurate and unbiased data. It involves a sequential explanatory strategy for data analysis and requires a minimum sample size of 60. The research includes 175 Polri members, 57 detainee families, and 114 detainees. Data collection is done through direct visits, and analysis techniques include descriptive statistics, Kruskall Wallis Difference Test, Spearman Correlation, and inferential statistics. Measurement validity is tested using AVE and factor loading, while reliability is assessed through Cronbach's Alpha. The structural model evaluation is based on R2 and path coefficient values. The results of this study indicate that all of the research hypotheses were accepted. Suggestions that can be given to related parties are improving communication, resources, disposition and bureaucratic structure and implementing transformational leadership styles so that the implementation of optimal prisoner care policies.